2012
DOI: 10.1097/hjh.0b013e328359311b
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure lowering to 160 mmHg or less using nicardipine in acute intracerebral hemorrhage

Abstract: SBP lowering to 160 mmHg or less using nicardipine appears to be well tolerated and feasible for acute ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We determined the safety and feasibility of systolic blood pressure reduction initiated within 3 hours from onset to <160 mmHg using intravenous nicardipine in 211 patients with acute spontaneous intracerebral hemorrhage (ICH) in the prospective, multicenter, observational Stroke Acute Management with Urgent Risk-factor Assessment and Improvement (SAMURAI)-ICH Study. 22 In its subanalysis, eGFR <60 mL/min/1.73 m 2 was positively associated with mRS score 5-6 (OR 5.87, 95% CI 1.87-19.34) and negatively associated with mRS score 0-2 (OR 0.21, 95% CI 0.07-0.54) at 3 months, after adjustment for known prognostic predictors including the initial NIH Stroke Scale score and hematoma volume. 12 In several other studies, the effects of CKD on neurological severity and outcomes of ischemic and hemorrhagic stroke were clarified.…”
Section: Chronic Kidney Disease Affects Stroke Severity and Outcomesmentioning
confidence: 93%
“…We determined the safety and feasibility of systolic blood pressure reduction initiated within 3 hours from onset to <160 mmHg using intravenous nicardipine in 211 patients with acute spontaneous intracerebral hemorrhage (ICH) in the prospective, multicenter, observational Stroke Acute Management with Urgent Risk-factor Assessment and Improvement (SAMURAI)-ICH Study. 22 In its subanalysis, eGFR <60 mL/min/1.73 m 2 was positively associated with mRS score 5-6 (OR 5.87, 95% CI 1.87-19.34) and negatively associated with mRS score 0-2 (OR 0.21, 95% CI 0.07-0.54) at 3 months, after adjustment for known prognostic predictors including the initial NIH Stroke Scale score and hematoma volume. 12 In several other studies, the effects of CKD on neurological severity and outcomes of ischemic and hemorrhagic stroke were clarified.…”
Section: Chronic Kidney Disease Affects Stroke Severity and Outcomesmentioning
confidence: 93%
“…Current American Heart Association (AHA) guidelines recommend the maintenance of systolic blood pressure to less than 140 mmHg in the setting of intracerebral hemorrhage with a long-term goal of SBP < 130 mmHg [14]. Table 4 below summarizes several additional studies with blood pressure parameters, IPH expansion, and neurologic decline in their patient cohorts [2, 3, 10, 13, 14, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Small studies have shown favorable outcomes with lower SBP targets. In a study of 211 patients in whom SBP was reduced to <160 mmHg within one hour of presentation, HE >33% of volume occurred in 17.1% of patients with neurological deterioration in 8.1% of patients [17]. Neurological deterioration was described as a ≥2 decrease in GCS or ≥4 increase in NIHSS score at 72 hr.…”
Section: Introductionmentioning
confidence: 99%
“…When controlling blood pressure in patients with ICH, a reduction in the SBP to <160 mmHg within 1.5 h after admission has been shown to significantly reduce hematoma expansion. 18 , 19 Strict management of SBP within the range of 120 to 160 mmHg also reportedly prevents hematoma expansion and poor outcomes. 20 Rapid, strict BP control is thus necessary in patients with untreated hypertension and liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%